THE IMPORTANCE OF SPORTS NUTRITION AND CORRECTION WATER-ELECTROLYTE BALANCE IN FOOTBALL - Adilbekov T. T. (Western European Studies, 2025)
The basic pattern of nutrition should be the correspondence between daily energy expenditure and daily caloric content of food. If the caloric content of food exceeds energy expenditure, this leads to fat deposition and digestive disorders. Insufficient caloric content with high energy expenditure leads to gradual exhaustion of the body, so to speak, to "selfeating"
Keywords: energy; water; carbohydrates